Perancangan Buku Tutorial Olah Kebugaran Tubuh Dengan Teknik Story Photography Sebagai Upaya Menyadarkan Pola Hidup Sehat - Alfarizhi, Mochammad Azam; Budiardjo, Hardman; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2017)
This research is focused on the problem about the imbalanced of healthy lifestyle even though the availability of facilities such as fitness facilities is quite enough. This research tries to provide alternative solutions by utilizing the attractiveness offered in research using story photography. The methodology applied in this research is qualitative approach, and the data is gathered through observation, interview, and literature review as a reference in creating a tutorial book of proper body fitness.Creating this tutorial book is necessary since people nowadays are not aware of the need to do physical activities and exercising. Because of that, we often meet people at a young age and are still fairly productive already attacked by the non- infectious diseases which is caused by unhealthy lifestyle, such as improper diet and never doing exercise. Thus, this tutorial book is created in order to help people in how to do body exercise by using objects that they can find around them. The content of the book will be explained through the combination of texts and pictures by applying the technique of story photography.Based on the research that has been done so far, the keywords in this tutorial book is worthy which means precious and valuable. The color that is used in the layout is the combination of green and yellow.Keywords: Design, Tutorial Book, Fitness, Story photography, Worthy.